2020
DOI: 10.32865/fire202062184
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Public School Leadership Capacity in Bishkek

Abstract: The purpose of this study was to provide insight into contextual factors predicting the extent of principals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Tschannen-Moran and Gareis ( 2004) emphasize that context matters in understanding principals' sense of efficacy. Findings from this study follow Bandura's model and align with findings by Sindhvad et al (2020) and Sindhvad (2009) which identified principals' sense of outcome expectancy for instructional supports as a factor influencing principal sense of efficacy, or capacity, for instructional leadership. However, while principals' sense of job satisfaction was a common factor influencing principal self-efficacy in both studies, time spent on key instructional leadership and school management tasks influenced principal self-efficacy in the current study.…”
Section: Contributions To the Literaturesupporting
confidence: 86%
See 4 more Smart Citations
“…Tschannen-Moran and Gareis ( 2004) emphasize that context matters in understanding principals' sense of efficacy. Findings from this study follow Bandura's model and align with findings by Sindhvad et al (2020) and Sindhvad (2009) which identified principals' sense of outcome expectancy for instructional supports as a factor influencing principal sense of efficacy, or capacity, for instructional leadership. However, while principals' sense of job satisfaction was a common factor influencing principal self-efficacy in both studies, time spent on key instructional leadership and school management tasks influenced principal self-efficacy in the current study.…”
Section: Contributions To the Literaturesupporting
confidence: 86%
“…Some studies examine the interplay of contextual factors on principal self-efficacy in the developing countries' context. Sindhvad et al (2020), andSindhvad (2009) investigated factors predicting sense of principal self-efficacy following reforms in Kyrgyzstan and the Philippines, respectively. Findings from both studies identified outcome expectancy for instructional supports (i.e.…”
Section: Principal Sense Of Efficacymentioning
confidence: 99%
See 3 more Smart Citations